Orientation behavior and thermal conductivity of liquid crystal polymer composites based on Three-Dimensional printing. (September 2022) - Luo, Fubin; Yang, Shuguang; Yan, Pinping; Li, Hongzhou; Huang, Baoquan; Qian, Qingrong; Chen, Qinghua
Graphical abstract: Abstract: Liquid Crystal Polymer (LCP) / hexagonal boron nitride (BN) composites are manufactured by three-dimensional (3D) printing approach. The results confirm that 3D printing can build up LCP bulk material with highly aligned nematic domains along the printing path. Also, BN can be orderly arrangement in matrix, exhibiting the same oriented direction as LCP molecules. The degree of orientation of BN is relevant to its lateral dimension. BN with a lateral size of 50 um in LCP matrix has a much higher degree of orientation compared with BN with a lateral size of 0.5 um and 5um. The well-ordered arrangement of BN and aligned LCP result that all of the printed sample has high thermal conductivity. The printed neat LCP bulk has a thermal conductivity 0.74 W m −1 K −1 parallel to the printing path direction, being filled with 20% mass fraction of BN, it can reach to 1.77 W m −1 K −1 .